The employment of temporary agency workers in the UK with or against the trade unions? - René Böheim; Martina Zweimüller (Johannes Kepler University of Linz, Department of Economics, 2009)
A firm's decision to employ agency workers may be perceived as a replace- ment of directly employed workers or as way to curb union power, which trade unions would oppose. Alternatively, trade unions may encourage the (tem- porary) employment of agency workers in a firm, if they manage to bargain higher wages for their members. We estimate the relationship between hir- ing agency workers and trade union activity at the workplace, in particular, the type of collective bargaining agreements. We use British data from the Workplace Employment Relations Surveys (WERS) of 1998 and 2004. The empirical association between the employment of agency workers and union strength is weak, but positive. Furthermore, workplaces with collective bar- gaining have lower wages in the presence of agency workers, suggesting that agency workers are hired against the unions.
Keywords: D21; J31; J40; 330; temporary work agency; collective bargaining; flexibility; Workplace Employment Relations Survey; Leiharbeit; Arbeitsnachfrage; Lohnniveau; Gewerkschaftsmitgliedschaft; Tarifpolitik; Arbeitsmarktflexibilität; Großbritannien